Exploring Social Learning Through Wiki in addition to Face to Face Interaction - Devaraj, K. (Journal of Engineering Education Transformations, 2015)
With the advent of social learning as a tool of instruction has shown a great promise in improving the sharing of information among the willful learners across the institutions. The current study is about the social learning activities in addition to the face-to-face class interaction. The experimental research was conducted with students enrolled in Basic Thermodynamics(BTD) course in the third semester of academic year 2014 and Turbo machines(TUM) in the fifth semester of academic year 2014.The students capability to adopt to the technology and use it as learning component in addition the class room teaching was tested. Students participation in peer review evaluation and learning from what their counterparts have commented on the solution were checked. Data were analyzed to show a significant increase in understanding the subject compared to the students who didn't participate in the Social learning. There were few minor drawbacks in implementing the social learning, but students showed lots of positive improvement in learning added to the classroom teaching.